PERENCANAAN KUALITAS PELAYANAN DAN KINERJA LAYANAN PELABUHAN: STUDI PADA PELABUHAN DI BANTEN - HM. Thamrin; Honny Fiva Akira Sembiring (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2016)
The role of ports in a transportation system, requires that each port has a basic framework of port development and development plans. Port service is a chain in supporting the smoothness of sea freight The research aims to examine and analyze the effect of planning dimensions of policies, procedures, standards, on the performance of port services in Banten Province The method used causality to analyze the existence or absence of mutual relationship between variables. The sample in this research is employee and port service section in Banten Region. Sampling method used is accidental sampling with employee criteria have been involved in planning and service sections amounted to 40 respondents. Analytical techniques used for hypothesis testing using Regression Analysis The results showed that the policy dimension affects the performance of services, procedures affecting performance, standards affect the performance, services and programs affect the performance of services Keywords: Service Planning, Service Performance and ports